Genomic and transcriptomic comparison of nucleotide variations for insights into bruchid resistance of mungbean (Vigna radiata [L.] R. Wilczek) - Liu, Mao-Sen (BMC Plant Biol, 2016)
BACKGROUND: Mungbean (Vigna radiata [L.] R. Wilczek) is an important legume crop with high nutritional value in South and Southeast Asia. The crop plant is susceptible to a storage pest caused by bruchids (Callosobruchus spp.). Some wild and cultivated mungbean accessions show resistance to bruchids. Genomic and transcriptomic comparison of bruchid-resistant and -susceptible mungbean could reveal bruchid-resistant genes (Br) for this pest and give insights into the bruchid resistance of mungbean. RESULTS: Flow cytometry showed that the genome size varied by 61 Mb (mega base pairs) among the tested mungbean accessions. Next generation sequencing followed by de novo assembly of the genome of the bruchid-resistant recombinant inbred line 59 (RIL59) revealed more than 42,000 genes. Transcriptomic comparison of bruchid-resistant and -susceptible parental lines and their offspring identified 91 differentially expressed genes (DEGs) classified into 17 major and 74 minor bruchid-resistance–associated genes. We found 408 nucleotide variations (NVs) between bruchid-resistant and -susceptible lines in regions spanning 2 kb (kilo base pairs) of the promoters of 68 DEGs. Furthermore, 282 NVs were identified on exons of 148 sequence-changed-protein genes (SCPs). DEGs and SCPs comprised genes involved in resistant-related, transposable elements (TEs) and conserved metabolic pathways. A large number of these genes were mapped to a region on chromosome 5. Molecular markers designed for variants of putative bruchid-resistance–associated genes were highly diagnostic for the bruchid-resistant genotype. CONCLUSIONS: In addition to identifying bruchid-resistance-associated genes, we found that conserved metabolism and TEs may be modifier factors for bruchid resistance of mungbean. The genome sequence of a bruchid-resistant inbred line, candidate genes and sequence variations in promoter regions and exons putatively conditioning resistance as well as markers detecting these variants could be used for development of bruchid-resistant mungbean varieties. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-016-0736-1) contains supplementary material, which is available to authorized users.